The Urgency of Mediation of the Religious Courts System on Islamic Law Perspective - Dharmayani, Dharmayani; Hermanto, Agus; Hidayat, Iman Nur; Rakhmat, Rakhmat; Setiawan, Agus (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2022)
Mediation is a Religious Court facility to resolve disputes outside the court; however, it is often found that the phenomenon of cases that have not been completed from the handling of mediation, for example, in family law disputes, is divorce. What is interesting to study is, what is the role and position of mediation in the Religious Courts? This paper aims to describe and analyze the role and function of mediation in the religious court environment, with the type of qualitative research in the form of library research. The conclusion of this study is that the court has carried out the mediation process with the position of the judge as a mediator. In contrast, the judge is the main role as well as the policymaker, so it becomes a very difficult task to be able to resolve cases outside the court plus, a case that has been entered into court are cases that have been screened through family, community and even customary approaches, and did not visit thoroughly and then refer to the court, what is often the problem is that the mediator who has been the judge, while the judge has a dual role, namely adjudicating and concurrently being a mediator